2021
DOI: 10.1007/s11010-021-04274-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of GTPase-activating protein ARHGAP26 in human cancers

Abstract: Rho GTPases are molecular switches that play an important role in regulating the behavior of a variety of tumor cells. RhoA GTPase-activating protein 26 (ARHGAP26) is a GTPase-activating protein and inhibits the activity of Rho GTPases by promoting the hydrolytic ability of Rho GTPases. It also affects tumorigenesis and progression of various tumors through several methods, including formation of abnormal fusion genes and circular RNA. This review summarizes the biological functions and molecular mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Rho GTPases have been demonstrated to influence diseased cell invasion and metastasis by controlling cytoskeletal contraction and cell membrane protrusion [ 28 ]. Negative regulators of Rac/Rho-like GTPases, GTPase-activating proteins (GAPs), reduce Rho GTPase activity by boosting the hydrolytic ability of Rho GTPases to convert activated GTP-binding status to inactivated GDP-binding status [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rho GTPases have been demonstrated to influence diseased cell invasion and metastasis by controlling cytoskeletal contraction and cell membrane protrusion [ 28 ]. Negative regulators of Rac/Rho-like GTPases, GTPase-activating proteins (GAPs), reduce Rho GTPase activity by boosting the hydrolytic ability of Rho GTPases to convert activated GTP-binding status to inactivated GDP-binding status [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in BTZ-resistant cells, we observed hypermethylation in the ARHGAP26 gene, which is involved in tumorigenesis and progression of human cancers. However, in various types of cancer, its expression changes significantly [ 29 ]. For instance, Qian et al demonstrated that ARHGAP26 hypermethylation resulted in reduced gene expression, which may be an early event in the pathogenesis of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that there are more genes with reduced expression than increased expression. We observed increased 5hmC levels in H3K4me3 regions in genes relating to cell proliferation, such as CDK6 [ 37 ] and ZMYND8 [ 38 ], and reduced 5hmC levels in H3K4me3 regions in genes that may be related to tumor suppression, such as ARHGAP26 [ 39 ] and GLI3 [ 40 ]. These results indicate that aberrant 5hmC levels result in unbalanced gene expression, which is an important mechanism of leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%